The Association between Sleep-Disordered Breathing and Magnetic Resonance Imaging Findings in a Pediatric Cohort with Chiari 1 Malformation - Reshma Amin; Priya Sayal; Aarti Sayal; Colin Massicote; Robin Pham; Suhail Al-Saleh; James Drake; Indra Narang (Canadian Respiratory Journal)
BACKGROUND: The prevalence of sleep-disordered breathing (SDB) reported in the literature for Chiari malformation type 1 (CM1) is uniformly high (24% to 70%). In Canada, there is limited access to pediatric polysomnography (PSG). Therefore, the identification of clinical features would be invaluable for triaging these children.